(untitled) - Billings, S. A. (Chichester, West Sussex, United Kingdom, 2013)
Nonlinear System Identification: NARMAX Methods in the Time, Frequency, and Spatio-Temporal Domains describes a comprehensive framework for the identification and analysis of nonlinear dynamic systems in the time, frequency, and spatio-temporal domains. This book is written with an emphasis on making the algorithms accessible so that they can be applied and used in practice.
Keywords: Nonlinear systems,Hệ thống phi tuyến